Optical break-down in alkali-haloid single crystals by laser focused radiation: the stage of local thermal explosion - Kononenko, V.G.; Volosyuk, М.А.; Volosyuk, А.V. (Вопросы атомной науки и техники, 2015)
Based on the results of experimental studying the pore formation kinetics and morphology in KCl single crystals under conditions of optical break-down by laser focused radiation were studied. It was shown that with observed parameters of the seats of energetic bursts and the dynamics of their formation, the optical break-down is similar to a powerful point explosion. In the heated area, a shock wave is generated. Having the velocity more than by an order exceeding the acoustic speed, the shock wave comes to the single crystal boundary earlier than other lattice disturbances and initiates formation of crowdions and their movement along atomic close-packed rows parallel to <110> type directions in both sublattices. From the condition of self-consistency between the flows of generated crowdions initiated by the supersonic shock wave and ones passing into unstressed crystal, it follows that the crowdion velocity would be also supersonic that was earlier predicted (A.M. Kosevich and L.S. Kovalyov). An assumption on possible participation of cumulative effect in the process has been made.